Heterogeneous multiple bank financing: does it reduce inefficient credit-renegotation incidences? - Christina E. Bannier (Frankfurt School of Finance & Management, 2007)
Small and medium-sized firms often obtain capital via a mixture of relationship and arm's-length bank lending. We show that such heterogeneous multiple bank financing leads to a lower probability of ineefficient credit foreclosure than both monopoly relationship lending and homogeneous multiple bank financing. Yet, in order to reduce hold-up and coordination-failure risk, the relationship bank's fraction of total firm debt must not become too large. For firms with intermediate expected profits, the probability of ineefficient credit-renegotiation is shown to decrease along with the relationship bank's information precision. For firms with extremely high or extremely low expected returns, however, it increases.
urn:nbn:de:101:1-20080827321
Keywords: D82; G21; L14; 330; Relationship lending; asymmetric information; financial distress; hold-up; coordination failure